(untitled) (KULT_online, 2013)
Looking at a picture is not only a process of looking at something, but also thinking about and interpreting it. The given anthology Bilder - Sehen - Denken is dedicated to precisely this interpretative field of Image Communication. The authors’ texts reflect on aspects of Image Studies and studies of empirical psychology. The texts show profoundly and interdisciplinarily how strongly processes of seeing and thinking are connected. They even indicate the unconscious processes of thinking and interpreting while perception occurs.